Peptide‐Conjugated Silver Nanoparticles for the Colorimetric Detection of the Oncoprotein Mdm2 in Human Serum. Issue 4 (19th January 2022) - Retout, Maurice; Gosselin, Bryan; Mattiuzzi, Alice; Ternad, Indiana; Jabin, Ivan; Bruylants, Gilles
Abstract: The development of efficient, reliable, and easy‐to‐use biosensors allowing early cancer diagnosis is of paramount importance for patients. Herein, we report a biosensor based on silver nanoparticles functionalized by peptide aptamers for the detection of a cancer biomarker, i. e. the Mdm2 protein. Silver nanoparticles (AgNPs) were produced and stabilized with a thin PEGylated‐calix[4]arene layer that allows (i) the steric stabilization of the AgNPs and (ii) the covalent conjugation of the peptide aptamers via the formation of an amide bond. These peptide‐conjugated AgNPs were then used to detect Mdm2 via a dual trapping strategy that was previously reported with gold nanoparticles (AuNPs). Our results showed that replacing AuNPs by AgNPs improves the detection limit by nearly one order of magnitude, down to 5 nM, while the high selectivity of the system and the stability of the particles provided by the calixarene coating allow the detection of Mdm2 in human serum. Abstract : Silver nanoparticles (AgNPs) coated with PEGylated calixarenes and conjugated to peptide aptamers were used for the colorimetric detection of Mdm2 in human serum via a dual‐trapping strategy. The calixarene‐based coating, despite its low thickness, provides a remarkable stability to particles. AgNPs allow to improve the limit of detection by almost one order of magnitude compared to similar system based on gold nanoparticles. This study highlights the interest of calixarene‐AgNPs for the development of colorimetric sensors.